[Much ado about something: the misterious brontídi] - Alessio Argentieri; Riccardo De Ritis; Giovanni Rotella; Camilla Bidini; Thomas Braun; Flavio Cecchini; Massimo Chiappini; Gaetano De Luca; Michele Di Filippo; Carlo Doglioni; Lionello Fittante; Fernandea Liggio; et al. (Acque Sotterranee)
[Article in Italian]